Seismic Retrofitting of Non-Engineering Masonry Houses using Polypropylene Band Meshes - Sathiparan, N.; Meguro, K. (My University, 2013)
This paper introduces a retrofitting technique aimed at preventing or prolonging the collapse of adobe (mud brick) houses under strong earthquakes. This technique uses common polypropylene packaging straps to form a mesh, which is then used to encase structural walls. The aim of this paper is to give an overview of the retrofitting technique’s development and implementation. The key development stages of static, dynamic and numerical testing are presented, showing that the proposed technique effectively prevents brittle masonry collapse and the loss of debris.
Keywords: Masonry; retrofitting; polypropylene band